A study on financial mechanisms used to manage public funds in the Local Government Authorities (LGAs) in Tanzania (Lighthouse Publishing, 2023)
Local Government Authorities all over the world have experienced mismanagement of public funds for many years. However, it has been confirmed that financial mechanisms are the bases for proper performance of Local Government Authorities. What have been not clear are on mechanisms used to manage public funds in the local government authorities. This study aimed to map mechanisms used to manage public funds in the local government authorities in Tanzania. The study used purposive sampling techniques in selecting study areas and respondents. Data were collected through in-depth interviews and focus group discussions. Both qualitative and quantitative approaches were used for analysis of data, but largely the qualitative approach was deployed. The study found that mechanisms such as financial laws, regulations and guidelines, segregation of duties, budget, technological systems, audit committee and frequent internal audit are mechanisms that local government authorities can use for management of public funds in Tanzania. The implication of this study is that, for proper management of public funds of any Local Government authority, financial mechanism is needed. The study recommends that, the Director of the local government authorities to abide by the existing financial mechanisms to control financial irregularities. This will also reduce audit queries and control leakage of public funds in the local government authorities.